Understanding public relations : theory, culture and society - Edwards, Lee (Lee M. S.) (SAGE Publications Ltd., 2018)
This text introduces a socio-cultural approach to public relations as a way of analysing the growing importance of public relations in its social, cultural and political contexts and brings theory to life with a range of case studies, including YouTube vlogging, the global fair trade movement and the 2016 EU referendum in the UK.